2015
DOI: 10.1109/twc.2015.2420099
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Networks Appear Poissonian Due to Strong Shadowing

Abstract: Geographic locations of cellular base stations sometimes can be well fitted with spatial homogeneous Poisson point processes. In this paper, we make a complementary observation. In the presence of the log-normal shadowing of sufficiently high variance, the statistics of the propagation loss of a single user with respect to different network stations are invariant with respect to their geographic positioning, whether regular or not, for a wide class of empirically homogeneous networks. Even in a perfectly hexag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 46 publications
1
65
0
Order By: Relevance
“…The BS positions form a stationary and ergodic point process Φ b ⊂ R 2 of density λ b , or a realization thereof, say a lattice network. As a result, the density of BSs within any region converges to λ b > 0 as this region's area grows [25]. In turn, the user positions conform to an independent point process Φ u ⊂ R 2 of density λ u , also stationary and ergodic.…”
Section: A Large-scale Modelingmentioning
confidence: 99%
“…The BS positions form a stationary and ergodic point process Φ b ⊂ R 2 of density λ b , or a realization thereof, say a lattice network. As a result, the density of BSs within any region converges to λ b > 0 as this region's area grows [25]. In turn, the user positions conform to an independent point process Φ u ⊂ R 2 of density λ u , also stationary and ergodic.…”
Section: A Large-scale Modelingmentioning
confidence: 99%
“…However, the Poisson distribution has the main advantage of being tractable, e.g., it is possible to compute different system performance metrics in a closed-form. Moreover, recent works by [20] and then later by [6] show that random shadowing and fading models render networks to appear Poisson to the user, even if the BSs do not form a PPP. In contrast to these works, here we are more focused on highlighting the spatial distribution of BSs.…”
Section: Discussionmentioning
confidence: 99%
“…2 It has recently been shown that, under a homogeneity condition, the BS positions are agnostic to the radio propagation waves, which mimics the BSs PPP distribution. 12,13 The performance of small cell networks is evaluated by fractional coverage characteristic to analyze the coverage probability, which captures the anisotropy of a single path-loss model. 2 The study concluded that the coverage probability with anisotropic path-loss models has been overestimated in low SIR regimes and has been underestimated in high SIR regimes.…”
Section: Figurementioning
confidence: 99%
“…The PPP model is constituted of BS, relay, and user parameters (eg, transmit power and path‐loss exponent) . It has recently been shown that, under a homogeneity condition, the BS positions are agnostic to the radio propagation waves, which mimics the BSs PPP distribution . The performance of small cell networks is evaluated by fractional coverage characteristic to analyze the coverage probability, which captures the anisotropy of a single path‐loss model .…”
Section: Introductionmentioning
confidence: 99%